The sword of Luchana : Baldomero Espartero and the making of modern Spain, 1793-1879 - Shubert, Adrian, 1953- (University of Toronto Press, 2021)
"Born into obscurity in a rural backwater of central Spain in the waning years of the eighteenth century, Baldomero Espartero (1793-1879) led a life resembling that of a character created by Stendhal or Gabriel García Márquez. As a seventy-five-year-old man he was offered--and turned down--the throne of an industrializing nation. He fought against Napoleon, Simón Bolívar, and other Latin American independence leaders; won a seven-year civil war, the Carlist War of 1833-1840; served as Regent for the child queen Isabella II; and spent years in exile in England. He governed as Prime Minister and also received multiple noble titles, including that of Prince, which was normally reserved for members of the royal family. By his sixties, Espartero represented an almost mythical figure. Based on comprehensive archival research in Spain, Argentina, and the United Kingdom, The Sword of Luchana explores the public and private lives of this archetypal nineteenth-century hero. Adrian Shubert gives voice to the mass of ordinary Spaniards who revered Espartero as the embodiment of liberty and freedom, and to Jacinta Martínez de Sicilia and Santa Cruz, his wife of more than fifty years who played a key role in his public career. Including unprecedented access to Espartero's personal papers, and set against the background of wars and revolutions in Spain and its American empire, The Sword of Luchana is a compelling account of the history of a crucial period of war, revolution, and political and social change."-- Provided by publisher.
Keywords: Espartero, Baldomero, -- 1793-1879.; Espartero, Baldomero, -- 1793-1879; Generals -- Spain -- Biography.; Prime ministers -- Spain -- Biography.; Spain -- History -- Isabella II, 1833-1868.; Spain -- Politics and government -- 1833-1868.; Généraux -- Espagne -- Biographies.; Premiers ministres -- Espagne -- Biographies.; Espagne -- Histoire -- 1833-1868 (Isabelle II); Espagne -- Politique et gouvernement -- 1833-1868.; BIOGRAPHY & AUTOBIOGRAPHY / Cultural, Ethnic & Regional / Hispanic & Latino.; Generals; Politics and government; Prime ministers; Spain; 1833-1868; Baldomero Espartero.; Carlist War.; Jacinta Martínez de Sicilia and Santa Cruz.; Latin American.; Queen Isabella II.; Spanish royalty.; biography.; independence.; modern Spain.; nineteenth century.; revolution.; Biography; Biographies; History; Biographies.